Wave absorber, wave absorbing structure including said wave absorber, and composition for wave absorber
By unevenly dispersing carbon fibers within a resin matrix, the radio wave absorber achieves high absorption efficiency while being thinner and lighter, addressing the size and weight limitations of existing absorbers for millimeter-wave radars.
Patent Information
- Application Number
- JP2024520365
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-05-12
- Filing Date
- 2023-04-25
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2043-04-25
AI Technical Summary
Existing radio wave absorbers for millimeter-wave radars are too thick and heavy, making them unsuitable for the growing demand for smaller and lighter sensors in applications like autonomous driving.
A radio wave absorber is developed by unevenly dispersing carbon fibers on one side of a resin matrix, reducing the amount of carbon fiber required while maintaining high radio wave absorption characteristics. The absorber is designed with 60-90% of the carbon fiber volume concentrated in the first half of the thickness, and includes hollow particles and carbon particles for enhanced performance.
The resulting radio wave absorber is thinner and lighter, achieving high radio wave absorption across the frequency range of 7.75GHz to 105GHz, with an absorption rate of 30% or more, making it suitable for advanced driver assistance systems and other applications.
Smart Images

Figure 0007661623000010 
Figure 0007661623000011 
Figure 0007661623000012
Abstract
Description
[Technical field]
[0001] The technique of the present disclosure relates to a radio wave absorber, a radio wave absorbing structure including the radio wave absorber, and a composition for a radio wave absorber. [Background technology]
[0002] In modern society, radio waves are used in a variety of fields, including broadcasting, communications, medicine, chemical analysis, positioning, remote control, etc. For example, millimeter wave radar, which uses radio waves in the frequency band of 30 to 300 GHz, is one of the key technologies that support autonomous driving of vehicles.
[0003] Millimeter-wave radar uses radio waves in the above frequency bands to measure the distance, speed, and angle to an object. Taking autonomous driving, one of the technologies in use, as an example, with the spread of ADAS (Advanced Driver Assistance Systems), millimeter-wave radars with long-distance detection of 76 to 77 GHz are being used as forward monitoring radars. Millimeter-wave radars detect the distance to an object by emitting millimeter waves and receiving the millimeter waves reflected by the object with a receiving antenna.
[0004] In millimeter wave radar devices, a shielding material that blocks radio waves is provided between the antenna and the control circuit, which prevents a decrease in detection accuracy caused by receiving millimeter waves reflected by objects other than the target (such as the road surface). As shielding members, for example, Patent Documents 1 and 2 disclose molded bodies and compositions containing resin and carbon fibers. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-161208 A [Patent Document 2] JP 2020-111730 A Summary of the Invention
[0006] Sensors such as millimeter wave radar are required to be compact and lightweight, so their constituent radio wave absorbers (shielding materials) also need to be thinner and lighter while maintaining high radio wave absorbing properties. An object of the technique of the present disclosure is to provide a radio wave absorber that has high radio wave absorbing properties and is thinner than conventional ones, and to provide a radio wave absorbing structure and a composition for a radio wave absorber that include the radio wave absorber.
[0007] As a result of intensive research, the present inventors have found that by distributing carbon fibers unevenly on one side in the thickness direction of the resin matrix, it is possible to obtain a thin radio wave absorber that has high radio wave absorption characteristics even when the amount of carbon fiber added is reduced, and have completed the technology of the present disclosure.
[0008] According to the technique of the present disclosure, the following radio wave absorber and the like are provided. 1. A composite material including a resin and a carbon fiber, A radio wave absorber, wherein 60 to 90% by volume of the entire carbon fibers are present within a region from the first surface to half of the entire thickness. 2. The radio wave absorber according to 1, wherein the carbon fiber content is 2 volume % or less of the total volume. 3. The radio wave absorber according to 1 or 2, further comprising hollow particles in an amount of 10% by volume or less of the total volume. 4. The radio wave absorber according to any one of 1 to 3, wherein the carbon fibers have an average length of 100 to 4000 μm. 5. The radio wave absorber according to any one of 1 to 4, wherein the resin has an organosiloxane structure represented by the following formula (1): [ka] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. 6. The radio wave absorber according to any one of 1 to 5, further comprising carbon particles in an amount of 10% by volume or less of the total volume. 7. The radio wave absorber according to any one of 1 to 6, which has an absorption amount of 30% or more of radio waves in the entire frequency range from 7.75 GHz to 105 GHz. 8. A radio wave absorber according to any one of 1 to 7, The radio wave absorber includes a radio wave reflector laminated on a surface side where the carbon fibers are unevenly distributed, The radio wave absorbing structure has a thickness of 200 to 500 μm. 9. The radio wave absorbing structure according to 8, having an absorption amount of 30% or more of radio waves in the entire frequency range from 9.75 GHz to 105 GHz. 10. A composite material comprising a resin having an organosiloxane structure represented by the following formula (1), carbon fibers, hollow particles, and carbon particles, The content of the carbon fiber in the solid content is 2% by volume or less, The content of the hollow particles in the solid content is 10% by volume or less, A radio wave absorber composition, wherein the content of the carbon particles in the solid content is 10 volume % or less. [ka] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
[0009] According to the technique of the present disclosure, it is possible to provide a thin wave absorber having high wave absorbing properties. It is also possible to provide a wave absorbing structure including the wave absorber and a composition for a wave absorber. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view of a radio wave absorber according to an embodiment of the disclosed technique. [Diagram 2] 1 is a schematic cross-sectional view of a radio wave absorbing structure according to an embodiment of the disclosed technique; [Diagram 3] FIG. 1 is a diagram showing the difference in complex dielectric constant between the wave absorbers produced in Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Radio wave absorber] The radio wave absorber according to one embodiment of the disclosed technique includes a resin and carbon fibers, and 60 to 90% by volume of the total carbon fibers are present in a region from the first surface to halfway through the total thickness. 1 is a schematic cross-sectional view of a radio wave absorber according to one embodiment of the disclosed technique. The radio wave absorber 1 is a sheet containing resin and carbon fibers and having a thickness T. The distance between the first surface 11 and the second surface 12, i.e., the thickness, is T. In this embodiment, 60 to 90% by volume of the total carbon fibers are present in a region A extending from the first surface 11 to half the total thickness T (thickness t=0.5T). That is, the carbon fibers are more unevenly distributed in the region A on the first surface 11 side than in the region B on the second surface 12 side. Note that the carbon fibers are uniformly distributed without uneven density in the horizontal direction (the surface direction where the radio waves hit). By distributing the carbon fibers unevenly on the first surface 11 side, it is possible to improve the radio wave absorption properties compared to the case where the same amount of carbon fibers are uniformly dispersed. If the ratio of carbon fibers in region A of the radio wave absorber 1 is low, a network between the carbon fibers cannot be formed well, resulting in a low dielectric constant of the radio wave absorber 1. Furthermore, if the carbon fibers settle and are excessively concentrated in region A, the dielectric constant of the radio wave absorber 1 will deviate from the appropriate level.
[0012] The ratio (volume %) of carbon fibers present in region A is determined by measuring the sample with a microfocus X-ray CT device, reconstructing a 3D image with image analysis software, and extracting the carbon fibers three-dimensionally based on the contrast of the image data due to the difference in the X-ray absorption coefficients of the resin and carbon fibers. Details will be described in the Examples.
[0013] The proportion of carbon fibers present in region A is preferably 65 to 90% by volume, and particularly preferably 66 to 90% by volume. The constituent members of the radio wave absorber will be described below.
[0014] <Resin> Resins used in this embodiment include silicone resins, epoxy resins, phenolic resins, polyurethane resins, thermosetting polyimides, unsaturated polyester resins, alkyd resins, etc. These resins can be used alone or in combination of two or more. It is preferable to use an appropriate hardener depending on the type of resin.
[0015] In one embodiment, a resin having an organosiloxane structure is preferred because it is easy to adjust the dielectric constant of the wave absorber. Examples of the organosiloxane structure include a structure represented by the following formula (1). [ka] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
[0016] In formula (1), R 1 and R 2 The halogen atoms each independently represent include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom. 1 and R 2 Examples of the alkyl groups each independently represent include methyl, ethyl, n-propyl, isopropyl, various butyl groups (the term "various" refers to both linear and branched butyl groups, and the same applies below), various pentyl groups, and various hexyl groups. 1 and R 2 The alkoxy group represented by each independently is exemplified by those in which the alkyl group moiety is the above-mentioned alkyl group. 1 and R 2 Examples of the aryl group that each independently represents include a phenyl group and a naphthyl group.
[0017] R 1 and R 2are preferably all hydrogen atoms, alkyl groups having 1 to 6 carbon atoms, alkoxy groups having 1 to 6 carbon atoms, or aryl groups having 6 to 12 carbon atoms, and more preferably all methyl groups.
[0018] Examples of resins having an organosiloxane structure include polyorganosiloxanes such as polydimethylsiloxane. In one embodiment, the resin having an organosiloxane structure is preferably a copolymer having a structure represented by the above formula (1) and another structure. By using the copolymer, it may be possible to easily adjust the viscosity during the production of the radio wave absorber.
[0019] An example of a copolymer having a structure represented by the above formula (1) and another structure is a polycarbonate-polyorganosiloxane copolymer. The polycarbonate structure of the copolymer includes a structure represented by the following formula (2). [ka] (In the formula, R 3 and R 4 each independently represents a halogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms. X represents a single bond, an alkylene group having 1 to 8 carbon atoms, an alkylidene group having 2 to 8 carbon atoms, a cycloalkylene group having 5 to 15 carbon atoms, an arylene group having 6 to 12 carbon atoms, a cycloalkylidene group having 5 to 15 carbon atoms, a fluorenediyl group, an arylalkylene group having 7 to 15 carbon atoms, an arylalkylidene group having 7 to 15 carbon atoms, -S-, -SO-, -SO2-, -O-, or -CO-.
[0020] In formula (2), R 3 and R 4 The halogen atoms each independently represent include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. R 3 and R 4Examples of the alkyl groups each independently represent include methyl, ethyl, n-propyl, isopropyl, various butyl groups, various pentyl groups, and various hexyl groups. 3 and R 4 The alkoxy groups each independently represent include those in which the alkyl moiety is the above-mentioned alkyl group.
[0021] Examples of the alkylene group represented by X include a methylene group, an ethylene group, a trimethylene group, a tetramethylene group, and a hexamethylene group, and an alkylene group having 1 to 5 carbon atoms is preferable. Examples of the alkylidene group represented by X include an ethylidene group and an isopropylidene group. Examples of the cycloalkylene group represented by X include a cyclopentanediyl group, a cyclohexanediyl group, and a cyclooctanediyl group, and an alkylene group having 5 to 10 carbon atoms is preferable. Examples of the arylene group represented by X include a phenylene group, a naphthylene group, and a biphenylene group. Examples of the cycloalkylidene group represented by X include a cyclohexylidene group, a 3,5,5-trimethylcyclohexylidene group, and a 2-adamantylidene group, and an alkylidene group having 5 to 10 carbon atoms is preferable, and an alkylidene group having 5 to 8 carbon atoms is more preferable. The aryl moiety of the aryl alkylene group represented by X includes aryl groups having 6 to 14 ring carbon atoms, such as a phenyl group, a naphthyl group, a biphenyl group, an anthryl group, etc. The aryl moiety of the aryl alkylidene group represented by X includes aryl groups having 6 to 14 ring carbon atoms, such as a phenyl group, a naphthyl group, a biphenyl group, an anthryl group, etc.
[0022] a and b each independently represent an integer of 0 to 4, preferably 0 to 2, and more preferably 0 or 1. Among these, it is preferable that a and b are 0 and X is a single bond or an alkylene group having 1 to 8 carbon atoms, or that a and b are 0 and X is an alkylidene group, particularly an isopropylidene group.
[0023] For details of the polycarbonate-polyorganosiloxane copolymer, see, for example, WO2019 / 131973.
[0024] <Carbon fiber> As the carbon fiber, either pitch-based carbon fiber or PAN-based carbon fiber can be used. The carbon fiber may be used alone or in combination of two or more types.
[0025] In one embodiment, the content of carbon fiber in the entire wave absorber is 2% by volume or less. The wave absorber of this embodiment can efficiently exhibit wave absorbing performance with a smaller amount of carbon fiber than conventionally by distributing the carbon fibers unevenly. The content of carbon fiber may be 1.8% by volume or less, or may be 1.5% by volume or less. The content of carbon fiber may be 0.5% by volume or more, or may be 0.8% by volume or more.
[0026] The average length of the carbon fibers is preferably 100 μm to 4000 μm. Within this range, high absorption properties can be obtained with a small amount of carbon fibers. The average length of the carbon fibers may be 150 μm or more, or may be 200 μm or more. The average length herein refers to the average value of the lengths of 25 randomly selected carbon fibers measured with a scanning electron microscope (SEM). The average length is the average length of the carbon fibers (raw material) during the production of the radio wave absorber. It is preferable that the average length of the carbon fibers in the radio wave absorber after production is also within the above range.
[0027] <Optional ingredients> In one embodiment, the radio wave absorber preferably contains hollow particles. Since the hollow particles have a large difference in density from the carbon fibers, adding the hollow particles to the resin makes it easier to form uneven distribution of the carbon fibers in the thickness direction. Examples of hollow particles include ceramic balloons, glass balloons, and shirasu balloons.
[0028] The average diameter of the hollow particles (d50: median diameter) is preferably 1 / 2 or less of the average length of the carbon fibers. More preferably, it is 1 / 3 or less of the average length of the carbon fibers. The average diameter of the hollow particles is a value based on JIS Z 8819-1:1999.
[0029] The pressure resistance of the hollow particles is preferably 8 MPa or more. If the pressure resistance of the hollow particles is low, they are likely to crack when mixed with a resin, etc. The pressure resistance of the hollow particles is more preferably 10 MPa or more. The compressive strength is measured by the glycerol method in accordance with ASTM D3102-78.
[0030] The content of the hollow particles in the entire wave absorber may be 1 volume % or more, or 2 volume % or more, and may be 10 volume % or less, or 8 volume % or less.
[0031] In one embodiment, the wave absorber preferably contains carbon particles, which can provide an appropriate conductive loss and can convert the wave into heat and provide absorption. Examples of the carbon particles include acetylene black, furnace black, and channel black. The content of the carbon particles in the entire wave absorber may be 0.1 volume % or more, or 0.2 volume % or more, and may be 10 volume % or less, 5 volume % or less, or 3 volume % or less.
[0032] The radio wave absorber of the present embodiment may contain known resin additives within the scope capable of solving the problems. Examples of known resin additives include stabilizers against heat, light, ultraviolet rays, etc., lubricants, nucleating agents, plasticizers, antistatic agents, release agents, flame retardants, softeners, dispersants, antioxidants, coloring materials, etc. The total content of the above known resin additives is preferably 50% by mass or less, and more preferably 40% by mass or less, in the electromagnetic wave absorber.
[0033] <Manufacture of radio wave absorbers> The wave absorber of the present embodiment can be produced, for example, by mixing the above-mentioned resin, carbon fiber, and optional components as required, and forming the mixture into a sheet. For mixing, a known dispersing device such as a high-speed disperser, a sand grind mill, a basket mill, a triple roll mill, or a ball mill may be used as necessary. When mixing, the various components can be mixed at once or in portions so as to obtain a predetermined amount. The order of mixing the various components is not particularly limited.
[0034] An example of a method for producing the radio wave absorber of this embodiment is to mix the above-mentioned components with a thermosetting resin (liquid before curing) or a solution in which a resin is dissolved in a solvent, form the mixed liquid into a sheet of a desired thickness by cast film formation, applicator film formation, or the like, and heat it. In this method, the uneven distribution state of the carbon fibers can be controlled by the standing time of the mixed liquid before heating. The standing time and heating time of the mixed liquid can be appropriately adjusted taking into consideration the viscosity of the resin or resin solution used, the solvent used, and the like. The concentration of the fixed component in the mixed solution is determined so as to obtain an appropriate film thickness for the frequency at which the maximum absorption capacity of the radio wave absorber is obtained, and is preferably 80 mass % or less and 5 mass % or more.
[0035] In this embodiment, the thickness of the radio wave absorber (T in FIG. 1) is preferably 200 to 500 μm. In this embodiment, by distributing the carbon fibers unevenly, radio wave absorbing performance can be efficiently achieved with a smaller amount of carbon fibers than before. Therefore, the thickness can be made thinner than before. The thickness of the radio wave absorber may be 400 μm or less, or may be 350 μm or less.
[0036] [Radio wave absorbing structure] A radio wave absorbing structure according to one embodiment of the disclosed technique includes the radio wave absorber of the present disclosure described above and a radio wave reflector laminated on the surface of the radio wave absorber on which carbon fibers are unevenly distributed. 2 is a schematic cross-sectional view of a radio wave absorbing structure according to one embodiment of the disclosed technique. The radio wave absorbing structure 2 has a structure formed by laminating a radio wave absorber 1 on one surface of a radio wave reflector 21. In this case, the side of region A where the carbon fibers are unevenly distributed is formed on the radio wave reflector 21. This makes it possible to improve the radio wave absorption properties compared to a case where the same amount of carbon fibers are uniformly dispersed.
[0037] The radio wave reflector is not particularly limited as long as it has the property of reflecting radio waves without transmitting them, such as a metal plate, a metal foil, a metal film, etc. Note that a resin layer such as a general adhesive layer may be formed between the radio wave absorber and the radio wave reflector. The radio wave absorbing structure can be manufactured, for example, by directly depositing the radio wave absorber 1 on the radio wave reflector 21 or by attaching the radio wave reflector 21 to the radio wave absorber 1.
[0038] Although a sheet-like radio wave absorbing structure is shown as an example in FIG. 2, the radio wave absorbing structure of this embodiment is not limited to a planar body such as a sheet, and can be appropriately shaped according to the area where it is used.
[0039] The radio wave absorber and radio wave absorbing structure of the present disclosure have high radio wave absorbing performance over the entire frequency range from 75 GHz to 105 GHz, specifically, the amount of radio waves absorbed over the entire frequency range from 75 GHz to 105 GHz can be 30% or more. In particular, in the frequency range (75 to 80 GHz) of millimeter wave radar capable of detecting long distances, it is possible to increase the amount of radio wave absorption to 30% or more, 50% or more, or 60% or more.
[0040] [Composition for radio wave absorber] The composition for a wave absorber of the present disclosure contains a resin having an organosiloxane structure represented by the following formula (1), carbon fibers, hollow particles, and carbon particles, wherein the content of the carbon fibers in the solid content is 2% by volume or less, the content of the hollow particles in the solid content is 10% by volume or less, and the content of the carbon particles in the solid content is 10% by volume or less. [ka] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
[0041] Specific constituent members, blending, suitable examples, etc. of the composition for a wave absorber of this embodiment are the same as those of the above-mentioned wave absorber. The composition for a wave absorber of this embodiment can contain known resin additives within the range in which the problem can be solved. The composition for a wave absorber of this embodiment may further contain a solvent. When the composition contains a solvent, the concentration of the fixed content in the composition is preferably 80 mass % or less, and preferably 5 mass % or more. The solvent is not particularly limited, and examples of the solvent that can be used include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), cyclopentyl methyl ether (CPME), and mixtures thereof. EXAMPLES
[0042] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples. In the following, unless otherwise specified, the temperature and pressure conditions were approximately at room temperature (usually 25°C) and normal pressure (usually 0.1013 MPa).
[0043] Example 1 Silicone resin (polydimethylsiloxane: Dow-Toray Industries, Inc., main material of Silpot184 (registered trademark)) 98.9 vol. % (after curing) and carbon fiber (middle fiber, Nippon Graphite Fiber Co., Ltd., XN-100-25M, average length 250 μm) 1.1 vol. % were mixed and stirred at 2000 rpm for 2 minutes using a planetary centrifugal mixer (Awatori Rentaro ARE-310). To the resulting mixture, 1 part (volume ratio) of a hardener, Silpot184 (registered trademark), was added to the main material 10 parts by volume, and the mixture was further stirred and mixed at 2000 rpm for 2 minutes, and then degassed at 2000 rpm for 2 minutes. The degassed mixture was poured into a 10 cm square aluminum container and left to stand for 50 minutes. After that, the aluminum container was heated on a hot plate at 100°C for 40 minutes to harden the mixture, and the hardened product (cast film) was peeled off from the aluminum container to produce a radio wave absorber. In Example 1, the mixed liquid was left to stand for 50 minutes, so that the carbon fibers were concentrated in the lower part.
[0044] Example 2 A radio wave absorbing structure was produced in the same manner as in Example 1, except that the composition of the mixed liquid was changed as shown in Table 1, and the cured product (cast film) was not peeled off from the aluminum container but was instead laminated with the aluminum.
[0045] Examples 3 to 6 Except for changing the composition of the mixed solution as shown in Table 1, radio wave absorbers were produced in the same manner as in Example 1. In Examples 3, 5, and 6, similarly to Example 2, radio wave absorbing structures consisting of a laminate of aluminum and the cured material were produced without peeling the cured material from the aluminum container.
[0046] Examples 7 to 11 Each component was added to a mixed solvent of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF) and cyclopentyl methyl ether (CPME) (NMP:DMF:CPME=10.3:3.5:1.0 / weight ratio) at the volume ratios (excluding the mixed solvent) shown in Tables 1 and 2, and the mixture was mixed and stirred to obtain a mixed solution. The mixed liquid was poured into a 10 cm square aluminum container and left to stand for 20 minutes. After that, the aluminum container was heated on a hot plate at 140°C for 60 minutes to dry the mixed liquid, thereby producing a radio wave absorber as a cured product (cast film). In Examples 7 to 11, the carbon fibers could be concentrated in the lower part by leaving the mixed liquid still for 20 minutes, which was a shorter time than in Example 1. In Example 9, a radio wave absorbing structure was produced by laminating a radio wave absorber on an aluminum plate that served as a radio wave reflector.
[0047] Comparative Example 1 Each component was added at the volume ratio shown in Table 1, and a mixed solution was prepared in the same manner as in Example 1. The mixed solution was poured into a 10 cm square aluminum container, and without leaving the aluminum container standing, it was heated on a hot plate at 100°C for 40 minutes to harden, and the hardened product (cast film) was peeled off from the aluminum container to produce a radio wave absorber.
[0048] Comparative Examples 2 to 5 Aside from changing the composition of the mixed liquid as shown in Table 1, a radio wave absorber was produced in the same manner as in Example 1.
[0049] Comparative Example 6 Each component was added to a mixed solvent of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF) and cyclopentyl methyl ether (CPME) (NMP:DMF:CPME=10.3:3.5:1.0 / weight ratio) at the volume ratios shown in Table 2 (excluding the mixed solvent), and the mixture was mixed and stirred to obtain a mixed solution. The mixed liquid was poured into a 10 cm square aluminum container and left to stand for 60 minutes. After that, the aluminum container was heated on a hot plate at 140°C for 60 minutes to harden the mixture, and the hardened product (cast film) was peeled off from the aluminum container to produce a radio wave absorber.
[0050] The radio wave absorbers and radio wave absorbing structures produced in the examples and comparative examples were measured for the proportion of carbon fiber contained in the lower 50% region (region A in FIG. 1) of the radio wave absorber, and the radio wave absorbing characteristics.
[0051] <Method for measuring the percentage of carbon fiber contained in the lower 50% of the radio wave absorber> The radio wave absorber was cut into 8mm x 20mm squares to prepare samples. After measuring the samples with a microfocus X-ray CT device (SkyScan2211, manufactured by Bruker), a 3D image was reconstructed using image analysis software (TRI / 3D-VIE, manufactured by Ratoc Systems Engineering Co., Ltd.), and carbon fibers were extracted three-dimensionally based on the contrast of the image data due to the difference in the X-ray absorption coefficients of the resin and the additive (carbon fiber). The fiber length distribution of the extracted carbon fibers was analyzed and converted into volume to calculate the volume concentration (vol%).
[0052] <Radio wave absorption characteristics> The measurement of the radio wave absorption characteristics was carried out by the free space method. Equipment used: PNA microwave network analyzer N5227 (Keysight Technologies) Test conditions Atmosphere: Air Temperature: room temperature Frequency: 75GHz~105GHz (Table 1) Irradiation angle: vertical The measurement results are shown in Tables 1 and 2. [Table 1]
[0053] [Table 2]
[0054] The materials used are as follows: (resin) PDMS: Silicone resin (polydimethylsiloxane: Silpot184 (registered trademark), manufactured by Dow Toray Industries, Inc.) Resin A: polycarbonate-polyorganosiloxane copolymer produced in Production Example 2 described later Resin B: Polycarbonate-polyorganosiloxane copolymer produced in Production Example 3 described later (Carbon Fiber) · Middle Fiber (manufactured by Nippon Graphite Fiber Co., Ltd.) Average length 150μm (XN-100-15M) Average length 250μm (XN-100-25M) Average length 3000μm (XN-100-03Z) (hollow particles) Hollow glass beads (Potters Barotini Co., Ltd. Q-CEL 7040S) (Radio wave reflector) Aluminum plate (10cm square, 2mm thick) (others) Carbon particles (acetylene black, Denka Co., Ltd., Denka Black (100% pressed))
[0055] It can be seen from Tables 1 and 2 that the Examples have high absorption characteristics with an absorption characteristic amount of 30% or more at all frequencies. On the other hand, in Comparative Example 1, the radio wave absorption amount was less than 30% at all frequencies, despite having the same components as in Example 1. This is thought to be because the proportion of carbon fibers in the lower region of the radio wave absorber was as low as 51 volume %, so that a network between the carbon fibers could not be formed well, resulting in a low dielectric constant of the radio wave absorber.
[0056] 3 shows the complex dielectric constants (@76 GHz) of the wave absorbers produced in Example 1 and Comparative Example 1. As shown above, it can be confirmed that the complex dielectric constants are significantly different. In Comparative Examples 2, 3 and 5, which did not contain carbon fibers, the amount of radio wave absorption was less than 30% at all frequencies. In Comparative Example 4, the proportion of carbon fibers in the lower region of the radio wave absorber was low at 52 volume %, which is thought to be the reason why a network between the carbon fibers could not be formed well, resulting in a low dielectric constant of the radio wave absorber. In Comparative Example 6, the measurement of the radio wave absorption characteristics showed that the radio wave absorption amount was not 30% or more at all frequencies. This is thought to be because the mixture was left standing for a long time, the carbon fibers settled, and were excessively unevenly distributed on the first surface, causing the radio wave absorber to deviate from an appropriate dielectric constant.
[0057] [Production of Resins A and B (Polycarbonate-Polyorganosiloxane Copolymers)] Manufacturing Example 1 (Production of polycarbonate oligomers) Sodium dithionite was added to a 5.6% by mass aqueous solution of sodium hydroxide in an amount of 2000 ppm by mass relative to bisphenol A (BPA) to be dissolved later. Next, BPA was dissolved in the above aqueous solution to a concentration of 13.5% by mass, to prepare an aqueous solution of sodium hydroxide of BPA. The resulting BPA in aqueous sodium hydroxide solution was continuously introduced into a tubular reactor with an inner diameter of 6 mm and a length of 30 m at flow rates of 40 L / hr, 15 L / hr of methylene chloride, and 4.0 kg / hr of phosgene. The tubular reactor had a jacket, and the temperature of the reaction solution was kept below 40°C by passing cooling water through the jacket.
[0058] The reaction liquid that had passed through the tubular reactor was continuously introduced into a baffled tank reactor equipped with a swept-back impeller and having an internal volume of 40 L. A sodium hydroxide solution of BPA was introduced into the tank reactor at a flow rate of 2.8 L / hr, a 25% by mass sodium hydroxide solution at 0.07 L / hr, water at 17 L / hr, and a 1% by mass triethylamine solution at 0.64 L / hr, and the reaction was carried out. The reaction liquid overflowing from the tank reactor was continuously withdrawn and allowed to stand to separate and remove the aqueous phase, and the methylene chloride phase was collected to obtain a polycarbonate oligomer solution. The polycarbonate oligomer had a concentration of 341 g / L and a chloroformate group concentration of 0.71 mol / L.
[0059] Manufacturing Example 2 (Production of Resin A) A 1 L separable flask equipped with a baffle plate and a mechanical stirrer with a stirring blade was charged with 185 mL of the polycarbonate oligomer solution (PCO) produced in Production Example 1 above, 445 mL of methylene chloride, 55 g of allylphenol-terminated polydimethylsiloxane having an average chain length n of 37, and 0.104 mL (0.75 mmol) of triethylamine (TEA). With stirring, sodium hydroxide aqueous solution A (aqueous solution obtained by dissolving 1.0 g (26.2 mmol) of NaOH in 12 mL of ion-exchanged water) was added and polymerized for 20 minutes.
[0060] To the obtained polymerization solution, 9.8 g of a methylene chloride solution of p-tert-butylphenol (PTBP: manufactured by DIC Corporation) [PTBP: 1.8 g (12.1 mmol) dissolved in 6 mL of methylene chloride] and an aqueous sodium hydroxide solution C (a solution obtained by dissolving 9.3 g (32.0 mmol) of bisphenol A, 6.8 g (170.5 mmol) of NaOH, and 0.031 g (0.20 mmol) of Na2S2O4 in 100 mL of ion-exchanged water) were added, and polymerization was allowed to proceed for 20 minutes.
[0061] After the polymerization was completed, the polymerization solution was transferred to a separatory funnel and allowed to stand to separate into an organic phase and an aqueous phase. The organic phase was transferred to another separatory funnel and washed with 100 mL of 0.03 mol / L NaOH aqueous solution and 100 mL of 0.2 mol / L hydrochloric acid, successively. After that, washing with ion-exchanged water was repeated until the electrical conductivity of the aqueous phase after washing was 10 μS / m or less. The washed organic phase was transferred to a tray and dried overnight at 48° C. in an explosion-proof dryer (under nitrogen atmosphere) to form a sheet, which was then cut to obtain a flake-like PC-POS copolymer (resin A).
[0062] Production Example 3 (Production of Resin B) In a 1 L separable flask equipped with a baffle plate and a mechanical stirrer with a stirring blade, 185 mL of the polycarbonate oligomer solution (PCO) produced in the above Production Example 1, 445 mL of methylene chloride, 77 g of allylphenol-terminated polydimethylsiloxane having an average chain length n of 37, and 0.104 mL (0.75 mmol) of triethylamine (TEA) were charged. With stirring, sodium hydroxide aqueous solution A (aqueous solution obtained by dissolving 2.1 g (52.5 mmol) of NaOH in 24 mL of ion-exchanged water) was added, and the polycarbonate oligomer and allylphenol-terminated PDMS were polymerized for 20 minutes.
[0063] To the obtained polymerization solution, a methylene chloride solution of p-tert-butylphenol (PTBP: manufactured by DIC Corporation) [PTBP: 1.8 g (12.0 mmol) dissolved in 10 mL of methylene chloride] and an aqueous sodium hydroxide solution C (a solution obtained by dissolving 7.6 g (33.4 mmol) of bisphenol A, 5.8 g (144.3 mmol) of NaOH, and 0.015 g (0.1 mmol) of Na2S2O4 in 84 mL of ion-exchanged water) were added, and polymerization was carried out for 20 minutes.
[0064] After the polymerization was completed, the reaction solution was transferred to a separatory funnel and allowed to stand to separate into an organic phase and an aqueous phase. The organic phase was transferred to another separatory funnel and washed with 100 mL of 0.03 mol / L NaOH aqueous solution and 100 mL of 0.2 mol / L hydrochloric acid, successively. After that, washing with ion-exchanged water was repeated until the electrical conductivity of the aqueous phase after washing was 10 μS / m or less. The washed organic layer was transferred to a tray and dried overnight at 48° C. in an explosion-proof dryer (under a nitrogen atmosphere) to form a sheet, which was then cut to obtain a flake-like PC-POS copolymer (resin B). [Industrial Applicability]
[0065] The radio wave absorber of the present disclosure can be used as a member for absorbing radio waves in the millimeter wave region in vehicles, civil engineering structures, buildings, port facilities, ship facilities, bridges, power facilities, communication facilities, mechanical facilities, etc. Specifically, it is suitable as a radio wave absorbing and shielding member used in millimeter wave radar devices, electric and electronic devices, etc. used in ships, aircraft, vehicles, etc. In addition, it is suitable as an unwanted radio wave absorbing and shielding member in traffic infrastructure environments such as road guardrails, tunnel inner walls, and smart cities.
[0066] Although some embodiments and / or examples of the present invention have been described in detail above, those skilled in the art can easily make many modifications to these exemplary embodiments and / or examples without substantially departing from the novel teachings and advantages of the present invention, and therefore many such modifications are within the scope of the present invention. The contents of all documents cited in this specification and of the application from which this application claims priority under the Paris Convention are incorporated by reference in their entirety.
Claims
1. Resin and carbon fiber, A radio wave absorber, wherein 60 to 90 volume % of the entire carbon fibers are present within a region from the first surface to half of the entire thickness.
2. 2. The radio wave absorber according to claim 1, wherein the content of said carbon fibers is 2% by volume or less of the total volume.
3. 3. The radio wave absorber according to claim 1, further comprising hollow particles in an amount of 10% by volume or less of the total volume.
4. 3. The radio wave absorber according to claim 1, wherein the carbon fibers have an average length of 100 to 4000 μm.
5. 3. The radio wave absorber according to claim 1, wherein the resin has an organosiloxane structure represented by the following formula (1): 【Chemistry 6】 (In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
6. 3. The radio wave absorber according to claim 1, further comprising carbon particles in an amount of 10% by volume or less of the total volume.
7. 3. The radio wave absorber according to claim 1, which has an absorption amount of 30% or more of radio waves in the entire frequency range from 75 GHz to 105 GHz.
8. A radio wave absorber according to claim 1 or 2; The radio wave absorber includes a radio wave reflector laminated on a surface side where the carbon fibers are unevenly distributed, The radio wave absorbing structure has a thickness of 200 to 500 μm.
9. 9. The radio wave absorbing structure according to claim 8, wherein the amount of radio waves absorbed in the entire frequency range from 75 GHz to 105 GHz is 30% or more.
10. The composite material includes a resin having an organosiloxane structure represented by the following formula (1), carbon fibers, hollow particles, and carbon particles, The content of the carbon fiber in the solid content is 2% by volume or less, The content of the hollow particles in the solid content is 10 volume % or less, A radio wave absorber composition, wherein the content of the carbon particles in the solid content is 10 volume % or less. 【Chemistry 7】 (In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
Citation Information
Patent Citations
The radio wave absorbing plate
JP1985048294U
Radio wave absorption material
JP2000151179A
Electromagnetic wave absorber
JP2000232297A
Multilayer electric wave absorber
JP2004186546A
Conductive molded body and its manufacturing method
JP2007229989A